Challenges Faced by Social Workers as Members of Interprofessional Collaborative Health Care Teams - Ambrose-Miller, Wayne (Health Soc Work, 2016)
Interprofessional collaboration is increasingly being seen as an important factor in the work of social workers. A focus group was conducted with Canadian social work educators, practitioners, and students to identify barriers and facilitators to collaboration from the perspective of social work. Participants identified six themes that can act as barriers and facilitators to collaboration: culture, self-identity, role clarification, decision making, communication, and power dynamics. These findings carry important implications for interprofessional collaboration with social workers in health practice.